2014
DOI: 10.1111/wrr.12189
|View full text |Cite
|
Sign up to set email alerts
|

Costs of burn care: A systematic review

Abstract: Burn care is traditionally considered expensive care. However, detailed information about the costs of burn care is scarce despite the increased need for this information and the enhanced focus on healthcare cost control. In this study, economic literature on burn care was systematically reviewed to examine the problem of burn-related costs. Cost or economic evaluation studies on burn care that had been published in international peer-reviewed journals from 1950 to 2012 were identified. The methodology of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 140 publications
(197 reference statements)
1
61
1
Order By: Relevance
“…This result is consistent with previous cost studies that have examined the economic management of typical burn populations 2,5 . In our study, we found that for each day added to a patient’s stay, the patient care and facility fees included in this category contributed the largest additional proportion to overall costs.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This result is consistent with previous cost studies that have examined the economic management of typical burn populations 2,5 . In our study, we found that for each day added to a patient’s stay, the patient care and facility fees included in this category contributed the largest additional proportion to overall costs.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, the patients injured in the Taiwan event required increased and prolonged use of variable antibiotics and antifungal agents, and experienced additional waiting time for artificial skin substitutes to become available. Because of this, medication fees became a higher cost driver in this patient cohort compared to the cohorts in previous burn studies 2,6,16 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations